Epizootic Activity of Natural Plague Foci of the Russian Federation in 2008–2017 and Forecast for 2018 - N. V. Popov; A. A. Kuznetsov; A. N. Matrosov; V. M. Korzun; D. B. Verzhutsky; S. A. Vershinin; S. A. Kosilko; T. M. Innokent’eva; M. P. Grigor’ev; D. Yu. Degtyarev; E. V. Gerasimenko; V. M. Dubyansky; et al. (Проблемы особо опасных инфекций, 2018)
Objective of the study was to assess the condition of parasitic systems and activity of natural plague foci of the Russian Federation in 2008–2017. Epizooties of varying intensity were registered in East-Caucasian high-mountain, Gorno-Altai high-mountain, Tuva mountain, and Precaspian sandy natural foci. In 2017, plague epizooties were detected in the territory of Kosh-Agach District of the Republic of Altai and Mongun-Taiginsk, Ovyursk and Tes-Khemsky Kozhuuns in the Republic of Tyva, covering the area of 1921 km2. In order to decrease the risk of infection in the territory of Gorno-Altai high-mountain and Tuva mountain natural plague foci in 2017, a set of survey and preventive measures was carried out, providing for epidemiological welfare of the population. Substantiated has been epizootiological forecast for the retention of an adverse epidemiological situation in Gorno-Altai high-mountain and Tuva mountain plague foci in 2018. Increase in the likelihood of finding individually infected animals in Central-Caucasian high-mountain and Precaspian sandy natural plague foci is expected.